Kinetics of charge-dependent reversible condensation of reflectin nanostructures - Lychko, Iana (2025)
Funding Information: This work has received funding from Fundação para a Ciência e Tecnologia (Portugal) for projects PTDC/BII-BIO/28878/2017, PTDC/CTM-CTM/3389/2021, CPCA/15912/2022, and Research Unit on Applied Molecular Biosciences– UCIBIO (UIDP/ 04378/2020 and UIDB/04378/2020) and Associate Laboratory Institute for Health and Bioeconomy– i4HB (LA/P/0140/2020), and the support of INCD funded by FCT and FEDER under the project 01/SAICT/2016 no 02215. The authors thank FCT/MEC for the research fellowship SFRH/BD/147388/2019 for I. L. and 2022.11305.BD for C. S. Publisher Copyright: © 2024 RSC.